Posthatch Developmental Morphology of the Pancreas in Kuttanad Duck (Anas platyrhynchos domesticus) - Patki, Harshad Sudhir (Indian Journal of Veterinary Anatomy, 2020)
Posthatch developmental morphology of the pancreas was studied in Kuttanad ducks by using 78 female ducklings from the day of hatch to 24th week of age. On the day of hatch itself, pancreas was divisible into three morphologically distinct lobes, viz., dorsal, ventral and splenic lobes. It was observed that throughout the developmental period this lobar arrangement was maintained. In all age groups, the dorsal, ventral and splenic lobes extended longitudinally in parallel with the ascending and descending limbs of duodenum however, theduodenal loop extended well beyond the end of the pancreas. In all age groups from the day of hatch to the 24th week, among the three lobes the dorsal lobe of pancreas was the largest and splenic lobe was the smallest.The morphological characteristics of constituent pancreatic lobes were studied. The highlight of the study was the occurrence of splenic lobe consistently in all the age groups with a thin band like process extending from its proximal extremity culminating abruptly as a distinct bulb that has not been described previously.